2022
DOI: 10.3389/fenvs.2022.788248
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Global Patterns of Drought Propagation

Abstract: Drought is the most expensive natural hazard and one of the deadliest. While drought propagation through standardised indices has been extensively studied at the regional scale, global scale drought propagation, and particularly quantifying the space and time variability, is still a challenging task. Quantifying the space time variability is crucial to understand how droughts have changed globally in order to cope with their impacts. In particular, better understanding of the propagation of drought through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Then, the cross correlation between standardized indices was applied at each pixel. However, the different time series were previously prewhitened using an Autoregressive Integrated Moving Average (ARIMA) model to remove serial correlation (Fuentes et al, 2022). Thus, this analysis was applied to calculate the maximum correlation between lags of 0 and 24 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the cross correlation between standardized indices was applied at each pixel. However, the different time series were previously prewhitened using an Autoregressive Integrated Moving Average (ARIMA) model to remove serial correlation (Fuentes et al, 2022). Thus, this analysis was applied to calculate the maximum correlation between lags of 0 and 24 months.…”
Section: Methodsmentioning
confidence: 99%
“…In many regions of the world, there is little difference between SPI and SPEI variability, as demonstrated in analyses of their historical record. This is particularly true in nonarid regions, where drought is driven mostly by rainfall variability (Fuentes et al, 2022). However, in a world with high temperature increases due to climate change, these two drought definitions might diverge further, as PET might play a larger role in some regions (Noureldeen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is because there is enough subsurface flow to maintain streamflow (van Tiel et al, 2021). In addition, areas with more forest cover will witness longer meteorological to hydrological drought propagation (Fuentes et al, 2022).…”
Section: Propagationmentioning
confidence: 99%
“…Typically, meteorological drought is regarded as the beginning of a drought event; after the occurrence of meteorological drought, other drought phenomena occur, such as hydrological drought (Fendeková et al, 2018;Fuentes et al, 2022;Wang et al, 2021). However, there is a delay period from meteorological drought to hydrological drought (Ding et al, 2021;Xu et al, 2019;Onyutha, 2017;Cammalleri and Vogt, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A change in the environment may lead to the nonstationarity of the relationship between hydrological series (for example, precipitation and runoff series), which also occurs in the Luanhe River basin (Wang et al, 2016(Wang et al, , 2018(Wang et al, , 2020. Traditional drought prediction methods need to be further improved to adapt to nonstationary conditions (Wang et al, 2022;Zhao et al, 2018;Chen et al, 2021). Ren et al (2017) found that the conditional distribution model using large-scale climatic indices as covariates can improve the accuracy of meteorological drought forecasting in the Luanhe River basin.…”
Section: Introductionmentioning
confidence: 99%